2022
DOI: 10.1590/1980-220x-reeusp-2021-0556en
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in times of COVID-19: a scoping review

Abstract: Objective: to identify how the COVID-19 pandemic has influenced postpartum women in breastfeeding. Method: a scoping review, with a search in seven databases. Studies available in full, in English, Portuguese or Spanish, published from December/2019-April/2021 were included. The analysis was carried out by categorizing common themes. Results: 25 studies were included, grouped into five categories, presenting the influence of the pandemic: in the routine of breastfeeding care, evidencing preventive measures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
9

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
3
0
9
Order By: Relevance
“…Nesse sentido, a amamentação deve ser incentivada desde o início da gestação, de forma que haja uma conscientização acerca dos benefícios do aleitamento materno. Para isso, o profissional de saúde é indispensável na transmissão das informações acerca do aleitamento materno (Moura et al, 2017;Souza et al, 2022), no sentido de orientar as mães no período gestacional e na lactação, assistindo-as com atendimento de qualidade, permitindo ainda que sejam sanadas suas dúvidas, angústias, medos, crenças, de modo a proporcionar confiança na prática da amamentação (Santana, et al, 2013). E, para a consolidação desta prática, é importante o acompanhamento de pré-natal por equipe de enfermagem qualificada, havendo repasse de qualidade de informações sobre os benefícios da amamentação exclusiva, além de sanar dúvidas e receios relatados pela nutriz (Silva, et al, 2022).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nesse sentido, a amamentação deve ser incentivada desde o início da gestação, de forma que haja uma conscientização acerca dos benefícios do aleitamento materno. Para isso, o profissional de saúde é indispensável na transmissão das informações acerca do aleitamento materno (Moura et al, 2017;Souza et al, 2022), no sentido de orientar as mães no período gestacional e na lactação, assistindo-as com atendimento de qualidade, permitindo ainda que sejam sanadas suas dúvidas, angústias, medos, crenças, de modo a proporcionar confiança na prática da amamentação (Santana, et al, 2013). E, para a consolidação desta prática, é importante o acompanhamento de pré-natal por equipe de enfermagem qualificada, havendo repasse de qualidade de informações sobre os benefícios da amamentação exclusiva, além de sanar dúvidas e receios relatados pela nutriz (Silva, et al, 2022).…”
Section: Resultsunclassified
“…Considera-se como maior desencadeador do desmame precoce, a falta de informação ou informações conflitantes acerca da amamentação e seu processo, especialmente no que se refere aos profissionais da saúde, que devem estar capacitados para auxiliar na prevalência do aleitamento materno (Souza et al, 2022).…”
Section: Introductionunclassified
“…It is possible that, during hospital admission, due to healthcare workers' fear of being infected despite having personal protective equipment and high rates of vaccination, less support was given to mothers with a COVID-19 infection with regard to BF. Likewise, given the need to isolate, which restricted the movement of these mothers once they had been diagnosed with the infection, it is also likely that they received less support following their discharge from hospital, and in this case they were only able to access off-site resources (for example, breastfeeding support groups or medical follow-up via telephone or video) [25][26][27] . In the same manner, a lack of information on the theoretical bene ts that BF could provide to children of mothers with a COVID-19 infection, could lead many mothers to rule out this option for fear that contact with their newborn could increase their risk of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The stress and anxiety brought about by the pandemic, along with the disruptions to healthcare services, have the potential to adversely affect breastfeeding outcomes [ 9 ]. A published review revealed that mothers who tested positive for COVID-19 were less inclined to initiate breastfeeding and had a shorter duration of exclusive breastfeeding in comparison to mothers who tested negative [ 4 ].…”
Section: Introductionmentioning
confidence: 99%